The Prevalence of Oral Flora in the Biofilm Microbiota of the Endotracheal Tube. Issue 5 (May 2016) - Bardes, James M.; Waters, Christopher; Motlagh, Hamed; Wilson, Alison
The endotracheal tube (ETT) is recognized as an independent factor for infection in intubated patients. The presence of biofilm contributes to the development of pneumonia. Standard culturing techniques are inadequate to detect many of the bacteria present in a biofilm. Delineation of the microbiota in the ETT is needed to further understand infections in ventilated patients. A prospective, observational study was performed at a university, Level I trauma center. Twenty ETT were collected at extubation. Bioluminal accretions were removed and quantified. DNA was extracted and 16S ribosomal RNA gene analysis performed using the Human Oral Microbe Identification Microarray. Twenty ETTwere evaluated. Mean age was 47.5 years (19–82). Five were smokers. Mean ventilator days was 3.6 ± 3.1. Mean intensive care unit days was 7.8 ± 6.3. In those ETT, 87 different bacterial species were identified. Mean number of bacterial species identified was 16 ± 9 (3–35). There was no relationship between duration of intubation and number of species ( P = 0.5). Nonsmokers had a greater variety of bacteria than smokers ( P = 0.03). Patients with pneumonia did not have a greater variety of bacteria ( P = 0.14). Parvimonas micra presence was associated with reintubation ( P = 0.01). The most common species in smokers were different from nonsmokers. There is a wide variety of bacteria present in an ETT, many of which cannot be cultured by standard means. Variation is not correlated to duration of intubation or accretion volume. Studies to evaluate these bacteria and their interaction with the biofilm may further delineate factors in development of infections.